NTN-1 attenuates amyloid-β-mediated microglial neuroinflammation and memory impairment via the NF-κB pathway and NLRP3 inflammasome in a rat model of Alzheimer's disease - Tianhang Wang; Yanchen Liu; Yidan Lu; Lijun Chi (Frontiers in Aging Neuroscience)
IntroductionNeuroinflammation driven by microglial activation represents a pivotal pathological mechanism underlying brain injury in Alzheimer's disease (AD), with NLRP3 inflammasome activation being a hallmark feature of this process. Netrin-1 (NTN-1) was recently shown to have potent anti-inflammatory and anti-apoptotic properties in a range of inflammatory diseases; however, its potential effect on neuroinflammation in AD treatment has not been well examined. Accordingly, this study aimed to investigate the effects of NTN-1 on cognitive impairment and to explore the anti-inflammatory properties related to the NLRP3 inflammasome and NF-κB signaling in Aβ1-42-induced rat models.MethodsWe assessed the effects of NTN-1 on neurobehavioral function, microglial activation and neuroinflammation mechanisms in Aβ1-42-treated rats using the Morris water maze test and Western blotting.ResultsOur results indicated that microinjections of NTN-1 attenuated Aβ1-42-induced memory and cognitive dysfunction and significantly inhibited microglial proliferation and NLRP3 inflammasome activation in the hippocampus and cortex of AD rats. Additionally, NTN-1 effectively prevented proinflammatory factor (IL1β and IL18) release and NF-κB signaling upstream activation.DiscussionOverall, the results of the present study indicated that exogenous NTN-1 treatment prevented neuroinflammation and cognitive deficits by inhibiting microglial activation, which is possibly mediated by the NF-κB signaling pathway and NLRP3 inflammasome activation in Aβ1-42-simulated rat models. NTN-1 emerges as a promising therapeutic candidate for mitigating microglia-mediated neuropathology in AD through its anti-inflammatory properties.